Serological Markers for Syphilis Among Persons Presenting With Syndromes Associated With Sexually Transmitted Infections: Results From the Zimbabwe STI Etiology Study. Issue 9 (September 2019) - Rietmeijer, Cornelis A.; Mungati, More; Kilmarx, Peter H.; Barr, Beth Tippett; Gonese, Elizabeth; Kularatne, Ranmini S.; Lewis, David A.; Klausner, Jeffrey D.; Rodgers, Luanne; Handsfield, H. Hunter
Abstract : Background: Syphilis prevalence in sub-Saharan Africa appears to be stable or declining but is still the highest globally. Ongoing sentinel surveillance in high-risk populations is necessary to inform management and detect changes in syphilis trends. We assessed serological syphilis markers among persons with sexually transmitted infections in Zimbabwe. Methods: We studied a predominantly urban, regionally diverse group of women and men presenting with genital ulcer disease (GUD), women with vaginal discharge and men with urethral discharge at clinics in Zimbabwe. Syphilis tests included rapid plasma reagin and the Treponema pallidum hemagglutination assay. Results: Among 436 evaluable study participants, 36 (8.3%) tested positive for both rapid plasma reagin and Treponema pallidum hemagglutination assay: women with GUD: 19.2%, men with GUD: 12.6%, women with vaginal discharge: 5.7% and men with urethral discharge: 1.5% ( P < 0.0001). Conclusions: Syphilis rates in Zimbabwe are high in sentinel populations, especially men and women with GUD. Abstract : Syphilis rates in Zimbabwe are high in sentinel populations, especially among men and women with genital ulcer disease.